Executive power over foreign affairs and the validity of compensation waiver clauses under international law and Philippine law: A critique of Vinuya, et al. V. Romulo - Martinez, Emil Angelo C. (Animo Repository, 2015)
In Vinuya, et al. v. Romulo, the Supreme Court held that the compensation claims of the victims against Japan for the atrocities committed during the Second World War, particularly the victims of sexual violence perpetrated by the Japanese Imperial Army in the Philippines, are barred because the Philippine government waived such claims on behalf of its nationals under the Treaty of San Francisco of 1951. The Court also reasoned that the question relating to the refusal of the Philippine government to espouse the claims of the petitioners against Japan before an international court or tribunal is a political question, and therefore the courts cannot rule on the matter. However, the legal reasoning of the Court falls short of substantive basis under international law and Philippine law. This paper seeks to examine the substantive content of international law with regard to treaty validity. This paper also aims to clarify the existing rules of international law that govern the rights of States in waiving reparation claims under international law. This paper will offer an alternative position - that the waiver clause in the Treaty of San Francisco is void under international law and Philippine law because it conflicts with non-derogable norms and rights recognized under international law. This paper will also aim to establish that the refusal of the Philippine government to espouse the claims of the petitioners is a justiciable issue.